2018
DOI: 10.31557/apjcp.2018.19.12.3435
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-to-Lymphocyte Ratio and Large Tumor Size Predict Microvascular Invasion after Resection for Hepatocellular Carcinoma

Abstract: Background: Recurrence after curative resection of hepatocellular carcinoma (HCC) is associated with early death and poor prognosis. Microvascular invasion (mVI) is strongly associated with disease recurrence. Although many studies have examined the relationship between various serum inflammatory indices and post-treatment prognosis, little is known about preoperative predictors of microvascular invasion in HCC. Methods: Patients who underwent curative hepatic resection for HCC at our institute from January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 59 publications
(67 reference statements)
0
16
0
Order By: Relevance
“…Of the 12 studies, only 7 clearly reported the association between the preoperative NLR level and MVI. 17,19,20,22,[25][26][27] The analysis of these seven studies arrived at a consistent conclusion (OR 1.62; 95% Cl 1.39, 1.89; P < 0.001) with a less heterogeneity (I 2 = 38%; P = 0.14) (Figure 2(b)). Among the seven studies, five were from China, one from Thailand, and one from Korea.…”
Section: Preoperative Nlr Level and MVI Riskmentioning
confidence: 56%
See 2 more Smart Citations
“…Of the 12 studies, only 7 clearly reported the association between the preoperative NLR level and MVI. 17,19,20,22,[25][26][27] The analysis of these seven studies arrived at a consistent conclusion (OR 1.62; 95% Cl 1.39, 1.89; P < 0.001) with a less heterogeneity (I 2 = 38%; P = 0.14) (Figure 2(b)). Among the seven studies, five were from China, one from Thailand, and one from Korea.…”
Section: Preoperative Nlr Level and MVI Riskmentioning
confidence: 56%
“…Finally, we identified 15 studies, all published between 2008 and 2018, which met the inclusion criteria. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Of the 15 studies, 12 were retrospective cohort studies 16-22, 24-27, 29 and three were case-control studies 23,28,30 (Table S2). Among the 12 cohort studies, nine were from China, one from England, one from Korea and one from Thailand.…”
Section: Search Results Study Characteristic and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21] Also, clinical studies showed that inflammatory indices can be used to predict the prognosis and the presence of MVI. [22][23][24][25][26][27] Therefore, it is necessary to combine inflammatory indices into the predictive models. The objective of our study was to develop nomograms based on imaging data as well as serum inflammatory data for MVI preoperative prediction in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…In various studies, tumor size has been demonstrated to be an effective preoperative predictive factor for MVI [6, 9, 15]. It is well established that the prevalence of MVI in HCC is strongly influenced by tumor size [16, 17]. As the tumor grows, the risk of MVI continues to increase.…”
Section: Discussionmentioning
confidence: 99%